Crucial Role of Extracellular Vesicles in Bronchial Asthma - Nagano, Tatsuya; Katsurada, Masahiro; Dokuni, Ryota; Hazama, Daisuke; Kiriu, Tatsunori; Umezawa, Kanoko; Kobayashi, Kazuyuki; Nishimura, Yoshihiro (International journal of molecular sciences, 2019)
Extracellular vesicles (EVs) are circulating vesicles secreted by various cell types. EVs are classified into three groups according to size, structural components, and generation process of vesicles: exosomes, microvesicles, and apoptotic bodies. Recently, EVs have been considered to be crucial for cell-to-cell communications and homeostasis because they contain intracellular proteins and nucleic acids. Epithelial cells from mice suffering from bronchial asthma (BA) secrete more EVs and suppress inflammation-induced EV production. Moreover, microarray analyses of bronchoalveolar lavage fluid have revealed that several microRNAs are useful novel biomarkers of BA. Mesenchymal stromal cell-derived EVs are possible candidates of novel BA therapy. In this review, we highlight the biologic roles of EVs in BA and review novel EV-targeted therapy to help understanding by clinicians and biologists.